"'We Wear the Mask': Three Movements on Survival, Resistance, and Activist Affect with deference to Paul Laurence Dunbar". Issue 1 (May 2023) - Alexander, Bryant Keith
In this short performative piece, the performer engages a critical juxtaposition of Paul Laurence Dunbar's classic poem, "We Wear the Mask" in relation to shifting currents of COVID-19, Racism, and Black Lives Matter; using the act of masking not just as a safety precaution against COVID-19 but as strategies of passing through oppression, and surviving under threat, with de-masking as a performative act of resistance against that which most threatens our humanity.